English literacy learning loss during the COVID-19 pandemic in Indonesia - Gin Gin Gustine; Sri Setyarini; Rojab Siti Rodliyah (Universitas Syiah Kuala, 2024)
This study explores the impact of the COVID-19-induced school closures in Indonesia on the decline of secondary school students learning, particularly in their English literacy. While numerous studies have delved into the repercussions of school closures on literacy skills in European countries, Australia, and the USA, such investigations have been relatively limited in Asia, particularly within the Indonesian context. Employing a qualitative approach for impact assessment, this research gathered data from diverse sources, including online surveys, one-on-one interviews, and focus group discussions. The survey involved 140 English teachers from four Indonesian provinces, including Java, Sumatra, Riau Islands, and Bali provinces. Ten English teachers were selected to participate in the individual online interviews, followed by a focus group discussion with four teachers. Within an inductive approach and thematic analysis framework, data were analysed, and five primary literacy skills emerged from the analysis that show a decline during the period of school closures: having critical thinking while reading, drawing inferences from texts, summarising text content, having good attitudes toward writing, and composing longer paragraphs. These initial findings, although on a small scale, are anticipated to help educators, school administrators, and policymakers in the Indonesian education sector in devising more effective plans for addressing unforeseen challenges in the future, including the development of programs to help students recover from learning loss.